Infrastructure and Innovation: Rethinking Digital Literacy for K-12 Learners - Irvani, Asep Irvan; Anisah, Ani Siti; Masripah (Yayasan Sinergi Kawula Muda, 2024)
In the wake of accelerating digital transformation, this study investigates how digital infrastructure, competency frameworks, and policy implementation influence digital literacy in K-12 education. The study employs a narrative review methodology, synthesizing findings from diverse literature databases including Scopus, Web of Science, and Google Scholar. Using keywords such as